If the values listed are those for x and you need to find y, you can solve for y as

2x + y = 4

y = 4 - 2x (subtract 2x)

Your first x value is -2, so y is

y = 4 - 2*(-2) (put -2 where x is in the equation)

y = 4 + 4 = 8

The first pair of coordinates is (x, y) = (-2, 8).

We can do the remaining x values in a list to save a little bit of effort and writing

y = 4 - 2*{-1, 0, 1, 2}

y = 4 - {-2, 0, 2, 4}

y = {6, 4, 2, 0}

The remaining coordinate pairs are

(-1, 6), (0, 4), (1, 2), (2, 0)

2x + y = 4

y = 4 - 2x (subtract 2x)

Your first x value is -2, so y is

y = 4 - 2*(-2) (put -2 where x is in the equation)

y = 4 + 4 = 8

The first pair of coordinates is (x, y) = (-2, 8).

We can do the remaining x values in a list to save a little bit of effort and writing

y = 4 - 2*{-1, 0, 1, 2}

y = 4 - {-2, 0, 2, 4}

y = {6, 4, 2, 0}

The remaining coordinate pairs are

(-1, 6), (0, 4), (1, 2), (2, 0)